Library and Information Science (LIS) Education: A conceptual framework towards "Europeisation" - Tammaro, Anna Maria (Journal of the Bangladesh Association of Young Researchers, 2011)
DOI: 10.3329/jbayr.v1i1.6950 Journal of Bangladesh Association of Young Researchers Vol.1(1) 2011 pp.1-13